Essays in value-added trade and U.S. labor market outcomes - Wang, Han (Kansas State University, 2019)
This dissertation contains three essays on how value-added trade affect the U.S. labor market outcomes. In the most recent presidential competition, we observed how voter angst against economic globalization had a considerable impact on the election results. This dissertation seeks to shed light on how the changes in exposure to value-added trade affect individual wages, the probability of being unemployed as well as the likelihood of being married with consideration of each worker’s occupation, the level of skill, and gender. In the first essay, we link U.S. industry-level value-added trade data with U.S. worker-level data from the Current Population Surveys from 1995 to 2009. We find that U.S. occupational exposure to value-added imports has a negative effect on the wages earned by intermediate-routine workers, which leads to wage polarization among American workers. In particular, the polarization of wages is driven by occupational exposure to value-added imports of final goods from middle-income countries, while exposure to final goods imported from high-income countries has a negative, albeit more fairly distributed, effect across U.S. workers’ wages. On the other hand, occupational exposure to value-added imports of intermediate goods from middle-income countries is associated with a positive wage effect for least-routine workers, signaling to the presence of strong complementarities between the group of least-routine workers and imports of intermediate goods from this group of countries. In the second essay, we investigate the contribution of the degree of occupation routineness and the level of a worker’s skill in determining the effects of U.S. exposure to value-added trade on U.S. labor market outcomes. We apply three main approaches to examine how the interplay between routineness and skills is essential in explaining the effects of U.S. exposure to value-added trade flows. First, we find that the increase in occupational exposure to value-added imports of final goods from middle-income countries is the primary driver of polarization of wages in the U.S. labor market within each skill group, where the effect on workers in the occupations with moderate levels of routineness is most adversely affected. Comparing the wage effects for workers within each routineness group, we find that skilled workers tend to face smaller pressure on their wages from import competition than the unskilled. Second, we examine the impact of exposure to value-added trade on the probability of being unemployed at the worker level. We show that an increase in exposure to value-added imports will raise the employment-related uncertainty for unskilled workers relative to skilled workers. Third, we estimate the transition costs across workers who have trade-induced occupation switches between two consecutive periods. Results suggest that occupation switch is very costly for all unskilled workers as well as for the skilled workers who are involved with the least-routine occupations. Notice that the effect of trade might not be gender-neutral. In the third paper, we complement the existing literature by providing evidence that increasing import exposure has differential effects on individual outcomes depending on the workers’ gender and on the degree of routineness of their occupations. We explore the effects of gender-specific exposure to value-added trade on individual outcomes such as wages, the probability of being unemployed, and the likelihood of being married. Despite that the male-specific exposures to value-added trade are highly comparable to those female-specific measures, we find it is powerful enough to distinguish their differential effects across gender. We find that the effect of trade is symmetric across genders when it comes to wage effects but asymmetric in terms of the probability of being unemployed and in the likelihood of being married. Our findings on wages suggest that an increase in exposure to value-added imports has the most negative effect on intermediate-routine workers for both gender groups, which results in wage polarization for both groups. As for the probability of being unemployed, we find that the greater the male-specific exposure to value-added imports, the greater the chances of being unemployed for male workers in the intermediate-routine occupations, while the effects for other men are insignificant. In the case of female workers, rising import exposure is associated with an increase in the uncertainty related to unemployment for those in least-routine occupations. Finally, for the likelihood of getting married, the effect for female workers is insignificant regardless of the degree of routineness. In the case of men, the likelihood of getting married decreases for males in intermediate-routine occupations when exposure to imported final goods increases, while, on the other hand, males in least-routine occupations are more likely to get married with an increase in exposure to intermediate inputs.
Keywords: Value-added trade; U.S. labor market; Polarization of wages; Import exposure; Unemployment uncertainty; Skill